2017
DOI: 10.1063/1.4984766
|View full text |Cite
|
Sign up to set email alerts
|

Water-anion hydrogen bonding dynamics: Ultrafast IR experiments and simulations

Abstract: Many of water's remarkable properties arise from its tendency to form an intricate and robust hydrogen bond network. Understanding the dynamics that govern this network is fundamental to elucidating the behavior of pure water and water in biological and physical systems. In ultrafast nonlinear infrared experiments, the accessible time scales are limited by water's rapid vibrational relaxation (1.8 ps for dilute HOD in HO), precluding interrogation of slow hydrogen bond evolution in non-bulk systems. Here, hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(138 citation statements)
references
References 72 publications
7
131
0
Order By: Relevance
“…The reorientation of water along the OH bond vector is more sensitive to anion than cation due to the direct hydrogen bond between anion and the water hydrogen. Cations, on the other hand, limit the reorientation of the water dipoles, especially for the divalence and trivalence ones (Boisson et al, 2011;Buchner et al, 2004;Buchner & Hefter, 2009;Laage & Hynes, 2007, 2008b; Lin, Auer, & Skinner, 2009;Park & Fayer, 2007;Turton et al, 2008;Wachter et al, 2007;Yamada, Thompson, & Fayer, 2017;R. Zhang & Zhuang, 2013).…”
Section: Water Reorientation Dynamics Probed By Spectroscopic Techniquesmentioning
confidence: 99%
“…The reorientation of water along the OH bond vector is more sensitive to anion than cation due to the direct hydrogen bond between anion and the water hydrogen. Cations, on the other hand, limit the reorientation of the water dipoles, especially for the divalence and trivalence ones (Boisson et al, 2011;Buchner et al, 2004;Buchner & Hefter, 2009;Laage & Hynes, 2007, 2008b; Lin, Auer, & Skinner, 2009;Park & Fayer, 2007;Turton et al, 2008;Wachter et al, 2007;Yamada, Thompson, & Fayer, 2017;R. Zhang & Zhuang, 2013).…”
Section: Water Reorientation Dynamics Probed By Spectroscopic Techniquesmentioning
confidence: 99%
“…For SeCN -, the electric field at the position of the C projected onto the CN bond-vector does accurately predict the C − − − N stretching frequency, but this is largely due to a cancellation of effects. 26 Nevertheless, this phenomenological association of local electric field with vibrational frequency still strongly supports the concept that the vibrational frequency will be sensitive to molecular orientation.…”
Section: Temperature-dependent Spectral Diffusion Dynamicsmentioning
confidence: 65%
“…Theoretical work has shown that both electrostatics beyond the dipole approximation and chemical interactions like charge transfer play important roles in determining the C − − − N stretching frequency. 26,58,59 Nevertheless, if these interactions are vectorial in nature, i.e. they depend on the orientation of the molecule, then they can be incorporated into the conceptual framework of RISD.…”
Section: Temperature-dependent Spectral Diffusion Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Likewise,t he longest memory of inhomogeneity of the very strongly H-bonded excess proton in water, [19] was recently found to be only of the order of 200 fs. [18] Likewise,t he longest memory of inhomogeneity of the very strongly H-bonded excess proton in water, [19] was recently found to be only of the order of 200 fs.…”
Section: Angewandte Chemiementioning
confidence: 99%